2015
DOI: 10.5397/cise.2015.18.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal versus Parallel Plating for Distal Humeral Fractures

Abstract: In orthopedic trauma surgery, treatment of intraarticular distal humerus fractures is a challenge. With development of implants and biomechanical studies, surgical strategies with recommendations including preoperative computed tomography images, proper approaches and open reduction and internal fixation with dual plates have emerged. In addition, as an effort to provide stable fixation to permit early elbow motion, different methods of internal fixation, particularly plate configuration, have evolved. Using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several biomechanical studies reported parallel plating is more rigid than orthogonal plating. But clinical studies that prove parallel plating is superior than orthogonal plating is still not enough[ 19 , 20 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomechanical studies reported parallel plating is more rigid than orthogonal plating. But clinical studies that prove parallel plating is superior than orthogonal plating is still not enough[ 19 , 20 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus that whether the orthogonal or parallel plating is superior for fixation. [31][32][33] We used orthogonal plating because it provides better mechanical stability although it requires more extensive soft tissue dissection. The functional outcome was based upon the Mayo Elbow Performance Score which was excellent in 24 patients (60%), good in 8 patients (20%), fair in 6 patients (10%), and poor in 2 patients (5%).…”
Section: Discussionmentioning
confidence: 99%